Land Bank For Land Management And Distribution For The Advancement Of Economic Development - Meliala, May Susan (Inspiring Law Journal, 2024)
Based on the Research Results That Hermeneutic Philosophy provides a philosophical basis (ontological and epistemological) for legal science, or the philosophy of science from legal science. Because, in implementing legal science to solve a legal problem, for example in court, the interpretation activity is not only carried out on the legal text, but also on the reality that gives rise to the relevant legal problem (for example, determining relevant facts and their legal meaning). The development of legal science is based on the activity of interpreting legal texts to distill or extract legal rules that (implicitly) exist in the legal text and thereby determine the meaning and area of application. The legal product produced in this case is the formation of a land bank through Law Number 11 of 2020 concerning Job Creation with the aim of managing and distributing land in Indonesia to create comprehensive and fair economic development progress. Based on Article 125 of Law Number 11 of 2020 concerning Job Creation, the Central Government forms a land bank agency. The land bank agency as referred to in paragraph (1) is a special agency that manages land. The wealth of the land bank agency is separated state wealth. The land bank agency functions to carry out planning, acquisition, procurement, management, utilization and distribution of land. The land bank agency guarantees the availability of land in the context of a just economy for the public interest, social interests, national development interests, economic equality, land consolidation and agrarian reform